Isomerization of 5-Vinyl-2-norbornene Using Sodium-coated Catalysts - Oh, Ji Hee; Ahn, Byoung Sung; Han, Jeong-Sik; Lee, Sang Deuk; Kim, Seung Wook; Lee, Hyunjoo (WILEY-V C H VERLAG GMBH, 2008)
Various sodium-coated metal oxide catalysts were prepared using readily available supporting materials such as neutral gamma-Al2O3 (neutral alumina, N-Al2O3) basic gamma-Al2O3 (basic alumina, B-Al2O3), SiO2, MgO, and TiO2, and their catalytic activities were evaluated for the isomerization of 5-vinyl-2-norbornene (VNB) to 5-ethylidene-2-norbornene (ENB). Of various sodium-coated catalysts, Na/N-Al2O3 and Na/B-Al2O3 showed extremely high activities, resulting in quantitative conversion of VNB. Catalyst characterization and isomerization results clearly demonstrated that the presence of both strong basic sites (pK(BH) >= 27) and one-electron donor sites on the Na/Al2O3 is prerequisite for the isomerization of VNB to take place.
Keywords: SUPERBASIC CATALYSTS; ALKYLATION; SILICA